B‐Type natriuretic peptide suppression of neutrophil superoxide generation: mechanistic studies in normal subjects. (October 2014) - Liu, Saifei; Ngo, Doan TM; Stewart, Simon; Horowitz, John D; Chirkov, Yuliy Y
Summary Many acute cardiovascular disease states are associated with neutrophil infiltration of myocardium and subsequent release of superoxide (O2−) and myeloperoxidase (MPO), which contribute to inflammatory reactions. B‐Type natriuretic peptide (BNP) is known to exert anti‐inflammatory and antifibrotic effects, but it is not known whether these may include interactions with neutrophils. In neutrophils isolated from 20 healthy subjects, we assessed the effect of BNP on the 'neutrophil burst' (O2− production and MPO release) stimulated by phorbol myristate acetate (PMA) and N‐formyl‐methionyl‐leucyl‐phenylalanine (fMLP), respectively. Effects of BNP on cGMP accumulation, and the effects of the cell‐permeable cGMP analogue 8‐(4‐chlorophenylthio) guanosine‐cGMP (8‐p‐CPT‐cGMP) and protein kinase G (PKG) inhibition with KT5823 on the neutrophil–BNP interaction were also evaluated. B‐Type natriuretic peptide suppressed O2− release from neutrophils by 23 ± 6% (P < 0.001) and 24 ± 8% (P < 0.05) following PMA and fMLP stimulation, respectively. Although BNP did not significantly increase cGMP formation, 8‐p‐CPT‐cGMP suppressed both PMA‐ and fMLP‐induced neutrophil O2− release by 16% and 28%, respectively (P < 0.05). The PKG inhibitor KT5823 attenuated the effects of BNP on both fMLP‐ and PMA‐associated O2− production. Neither BNP nor 8‐p‐CPT‐cGMP significantly affected MPO release from neutrophils. Suppression of O2− release from neutrophils by BNP may contribute to its anti‐inflammatory and antifibrotic actions.